Physico-chemical characterization of açaí seed and fiber (Euterpe oleracea Mart.) through classical and instrumental methods - Santos, Matheus Maciel; Pasolini, Fernanda Souza; Costa, Ana Paula Oliveira (Brazilian Journal of Production Engineering, 2023)
The açaí tree fruit (Euterpe oleracea Mart.) has great importance in the Brazilian agroindustrial sector, being widely consumed in the country. The cultivation of açaí generates residues such as the seed and fiber, which are usually discarded without previous treatments. There are few data regarding the physical-chemical characterization of these residues, and the possibilities of its reuse have not been defined yet. In this context, this work aimed to study the physical -chemical and thermal characterization of the seed, the fiber and its extractives, through the analysis such as absolutely dried percentage, extractives in water, sodium hydroxide and organic solvent, ash content, lignocellulosic percentage, density and thermogravimetric analysis. The absolutely dried percentage was 90.% for fiber and 85.1% for seed, that showed a higher amount of extractives compared to the fiber, and both showed low levels of soluble extracts in organic solvent. The ash content was 1.40% for fiber and 3.41% for seed. The lignin contents obtained for seed and fiber were 25.1% and 24.8%, respectively. The cellulose content was 46.2% for fiber and 18.6% for seed. The average seed density was 1.27 g/cm3. All residues showed four stages of degradation in the TGA.